(untitled) (Journal of Philosophy Culture and Political Science, 2023)
The dominant trends in the political process and electoral strategies demonstrate de-ideologization, simplification of party programs and representations. Competition between parties at the present stage does not take place from the point of view of the classical confrontations "left-right" or "liberal-socialists", but shows the ability to solve an urgent problem. In this sense, the legitimacy of any party depends on the combination of the issues raised and the ability to solve them, while the party programs present a vision of problems with a performative character. Party programs during the period of election campaigns in Kazakhstan were studied in terms of measures taken and proposed, but not in terms of building legitimation and identification rhetoric. This article provides a content analysis of the content of party programs based on positional and polyvalent issues. The results show that Kazakhstan is not an exception among countries whose parties have taken a course towards de-ideologization of party programs. The analysis carried out shows that the programs of the first three parties turned out to be more polyvalent. Based on the results of the study, a conclusion is made about the nature of polyvalent and positional rhetoric from the point of view of political philosophy, and further trends in party building in the Republic of Kazakhstan are also evaluated. Keywords: legitimacy, positional and polyvalent issues, party programs, content analysis, Ochiai-Otsuki-Barkman coefficient